Hidrolisis Limbah Kulit Pisang (Musa acuminata) Menggunakan Katalis Asam untuk Produksi Bioetanol - Bahlawan, Zuhriyan Ash shiddieqy; Megawati, Megawati; Triwibowo, Bayu; Pratama, Alfiansyah Aji; Pradiza, Zefanya; Septiamurti , Anggun (REACTOR: Journal of Research on Chemistry and Engineering, 2022)
Banana is one of the fruits that can thrive in Indonesia. This plant is often found in tropical soils with slightly moist soil conditions. However, banana peels are underutilized and are only disposed of as agricultural waste. On the other hand, the carbohydrate content of banana peels is still quite high, reaching 12.2% so it can be used as raw material for making bioethanol. Carbohydrates in the substrate cannot be directly converted into bioethanol but need to be pretreated first to break down polysaccharides into monosaccharides. In this research, the pretreatment process of carbohydrate hydrolysis from banana peels into reducing sugars is studied. From the studies, the reducing sugar concentration was obtained with banana peels substrate concentration of 20 g/L, 5 M of sulfuric acid concentration, and an optimum hydrolysis time of 70 minutes with the obtained reducing sugar reach 16.82 g/L. Reducing sugar can be converted into bioethanol by fermentation process with S. cerevisiae yeast. It is hoped that these studies can provide an initial impact on the development of alternative energy based on biomass and utilization of banana peel waste.